PENGARUH GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, KINERJA KEUANGAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Nunik Nunik; Dwi Ermayanti Susilo (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This research aims to provide empirical evidence of the Influence of Good Corporate Governance, Corporate Social Responsibility, Financial Performance, and Corporate Size on Corporate Value. The type of data used in this study is skunder data consisting of financial statements and annual statements of banking companies listed on the Indonesia Stock Exchange. The methods carried out in this study are quantitative research methods using multiple linear regression analysis techniques and hypothesis tests processed with SPSS. With the population and sample in this study are all banking companies listed on the Indonesia Stock Exchange from 2018 - 2020. The sampling technique purposive sampling and obtained samples as many as 10 companies. Data analysis shows that Good Corporate Governance has a significant effect on the value of the company, Corporate Social Responsibility does not have a significant effect on the value of the company, . Financial Performance has a significant effect on the value of the company, and the size of the company has a significant effect on the value of the company. The coefficient of determination (R²) is 0.708. This means that in this study the variables good corporate governance, corporate social responsibility, financial performance and size of the company are able to affect the value of the company by 70.8% and the remaining 29.2% influenced by other factors